A 3D-printed, multi-modal microfluidic device for measuring nitric oxide and ATP release from flowing red blood cells. Issue 33 (12th August 2022) - Hayter, Elizabeth A.; Azibere, Samuel; Skrajewski, Lauren A.; Soule, Logan D.; Spence, Dana M.; Martin, R. Scott
Abstract : A 3D-printed multi-modal device was developed to simultaneously detect nitric oxide (NO) and adenosine triphosphate (ATP) in red blood cell suspensions. Abstract : In this paper, a 3D-printed multi-modal device was designed and fabricated to simultaneously detect nitric oxide (NO) and adenosine triphosphate (ATP) in red blood cell suspensions prepared from whole blood. Once a sample was injected into the device, NO was first detected ( via amperometry) using a three-electrode, dual-opposed, electrode configuration with a platinum-black/Nafion coated gold working electrode. After in-line amperometric detection of NO, ATP was detected via a chemiluminescence reaction, with a luciferin/luciferase solution continuously pumped into an integrated mixing T and the resulting light being measured with a PMT underneath the channel. The device was optimized for mixing/reaction conditions, limits of detection (40 nM for NO and 30 nM for ATP), and sensitivity. This device was used to determine the basal (normoxic) levels of NO and ATP in red blood cells, as well as an increase in concentration of both analytes under hypoxic conditions. Finally, the effect of storing red blood cells in a commonly used storage solution was also investigated by monitoring the production of NO and ATP over a three-week storage time.